Военно-историческая работа - Португальский Ричард Михайлович (Воениздат, 1990)
Экземпляры: КХ (20101207) / Инвентарный номер: 973721 / Цена: 0.80 / Сис.шифр: 68 / Авт.знак: П 60 / ГРНТИ: 78 / ББК: 68.41(2)